2022
DOI: 10.3390/metabo12100996
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq Analysis of Brown Adipose Tissue and Thyroid of Newborn Lambs Subjected to Short-Term Cold Exposure Reveals Signs of Early Whitening of Adipose Tissue

Abstract: During the early postnatal period, lambs have the ability to thermoregulate body temperature via non-shivering thermogenesis through brown adipose tissue (BAT), which soon after birth begins to transform into white adipose tissue. An RNA seq approach was used to characterize the transcriptome of BAT and thyroid tissue in newborn lambs exposed to cold conditions. Fifteen newborn Romney lambs were selected and divided into three groups: group 1 (n = 3) was a control, and groups 2 and 3 (n = 6 each) were kept ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…It has been reported that shivering contributes 60% to the thermogenesis of newborn lambs [ 98 ]. The canine neonate has a low capacity to perform thermogenesis with tremors because it uses other physiological mechanisms, such as respiratory and cardiovascular pattern changes.…”
Section: Newborn Thermoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that shivering contributes 60% to the thermogenesis of newborn lambs [ 98 ]. The canine neonate has a low capacity to perform thermogenesis with tremors because it uses other physiological mechanisms, such as respiratory and cardiovascular pattern changes.…”
Section: Newborn Thermoregulationmentioning
confidence: 99%
“…During this procedure, oxygen consumption and the anaerobic capacity of muscle fibers increase, leading to the oxidation of energy molecules such as carbohydrates and fatty acids [34,96,97]. It has been reported that shivering contributes 60% to the thermogenesis of newborn lambs [98]. The canine neonate has a low capacity to perform thermogenesis with tremors because it uses other physiological mechanisms, such as respiratory and cardiovascular pattern changes.…”
Section: Shivering Thermogenesismentioning
confidence: 99%
“…In addition, Haughey [ 101 ] reported cold injuries in newborn Merino lambs reared at 1 °C, which animals have extensive catabolism of fat deposits regardless of colostrum intake. This is relevant in lambs because most of the fat reserves used to thermoregulate in newborns are derived from brown adipose tissue [ 102 ].…”
Section: Intrinsic Factors Affecting the Temperature In The Newborn B...mentioning
confidence: 99%